Evaluating the effect of insensitive high explosive residues on soil using an environmental quality index (EQI) approach - Persico, Federica; Coulon, Frederic; Ladyman, Melissa K.; Fernandez Lopez, Carmen; Temple, Tracey (Elsevier, 2023)
The environmental impact of Insensitive High Explosive (IHE) detonation residues to soil quality was assessed using a series of outdoor soil mesocosms. Two different soils were used including a pristine sandy soil and a land-degraded soil collected from a training range. Both soils were spiked with an IHE mixture comprised of 53 % NTO, 32 % DNAN and 15 % RDX at three different concentrations 15, 146 and 367 mg/kg respectively. The concentration levels were derived from approximate residues from 100 detonations over a 2 week training period. A set of five physico-chemical and biological indicators representative of the two soils were selected to develop environmental quality indexes (EQI). It was found that none of the concentrations tested for the pristine soil affected the chemical, biological and physical indicators, suggesting no decrease in soil quality. In contrast, the EQI for the degraded soil was reduced by 24 %, mainly due to a decrease in the chemical and biological components of the soil. Therefore, it is concluded that depending on the soil health status, IHE residues can have minor or severe consequences on soil health. Further studies are needed to determine the environmental impact of IHE on soil and water especially in the case where a larger number of detonations are more likely to be carried out on a training range.
Keywords: Soil quality; Soil assessment; DNAN; NTO; RDX